Connecting the Unconnected: Bridging the Digital Divide with Affordable Satellite Through Enabled Smartphones - Akhtar M.D. Samir; Mathur Gauri; Kravchenko Oleg; Rakhra Manik (E3S Web of Conferences, 2023)
In the current digital era, having connection to the internet is essential for economic opportunities, education, and communication. However, there is unequal access to these digital resources due to the ongoing global problem of the “digital divide”. In order to close this gap, this project investigates the creation of a satellite-connected, reasonably priced smartphone. Traditional terrestrial networks have their limitations, especially in isolated and rural locations where it can be difficult to access the internet. Furthermore, communication in metropolitan areas is hampered by worries about radiation from cellular towers. This method overcomes the constraints of conventional terrestrial networks to provide internet access to even the most remote locations by outfitting smartphones with satellite communication capabilities. This technology not only offers economic opportunities, education, and basic services, but it also lessens the need for traditional cellular towers in crowded places, which may allay worries about radiation exposure from towers. The study highlights how crucial it is to overcome technological obstacles, work with manufacturers, develop encouraging regulations, and run awareness efforts in order to promote the adoption of this ground-breaking strategy. The main conclusions indicate that, in addition to addressing connection and health issues, reasonably priced smartphones with satellite connectivity can make a substantial contribution toward bridging the digital divide and helping urban and impoverished communities. This study makes a very clear point: adopting smartphones with satellite capabilities can open the door to a more connected and just digital society.